Optimal Route Determination System (ORDS) for Pedestrian Safety - Ta, ThuHa (Universiti Teknologi PETRONAS, 2009)
A <;ommoll mea11s of traveli11g in (owns, <;ities am! <tarnPYs is walk:ing because t11er~; are many pavements and short-cuts not accessible by motor vehicles. Unfortunately, certain stretches are prone to risks such as high speed traffics and social crimes, hence the need for safe pedestrian routes. This paper proposes a map application designed for pedestrian safety that recommends the safest path based on user inset criteria, safe route determination algorithm and knowledge base. This application may find usage by people who travel alone such as working night shift, missing the last public transport or backpacking tours. The system gives priority to safe route based on database input before looking into the distance. The system is developed using internet aid wireless technology for ease of access. The contribution of this work is system design that provides the mentioned functionalities on handheld devices. iii